Diagenesis of the first member of Canglangpu Formation of the Cambrian Series 2 in northern part of the central Sichuan Basin and its influence on porosity - Zou, Bing; Qu, Haizhou; Zhao, Rongrong; Zhang, Lianjin; Zhang, Yu; Ma, Zike; Zhang, Xingyu; Huang, Qinyang; Mo, Qianwen; An, Hongyi; Pei, Yu (Frontiers in Earth Science, 2023)
In this paper, taking the first Member of the Canglangpu Formation of the Cambrian Terreneuvian in the northern central Sichuan Basin as an example, the diagenesis and its influence on reservoir quality are systemically studied based on the observations and identifications of cores, casts and cathodoluminescence thin sections. The results show that the rock types of the first Member of the Canglangpu Formation are complex, and the sand-bearing oolitic dolomite, sandy oolitic dolomite, sparry oolitic dolomite and fine-grained detrital sandstone are mainly developed. At the same time, the Cang 1 Member has experienced five types of diagenetic environments, including seawater, atmospheric freshwater, evaporative seawater, shallow burial, and medium-deep burial diagenetic environments. Moreover, the main diagenetic processes under different diagenetic environments include cementation, dissolution, compaction, pressure solution, dolomitization and tectonic rupture. According to the analysis, fabric-selective dissolution in atmospheric freshwater diagenetic environment, dolomitization in evaporative seawater environment, and non-fabric-selective dissolution, dolomitization and tectonic rupture in buried diagenetic environment are beneficial to the development of pores in the reservoir. However, cementation, compaction and pressure-solution in medium and deep burial environments, are unfavorable for the development of reservoir pores.